Hot-substrate deposition of all-inorganic perovskite films for low-temperature processed high-efficiency solar cells. Issue 6 (22nd January 2019) - Wang, Ze; Liu, Xiaodong; Lin, Yiwei; Liao, Yingjie; Wei, Qi; Chen, Haoran; Qiu, Jingjing; Chen, Yonghua; Zheng, Yonghao
Abstract : An excellent PCE of 13.8% was achieved for low-temperature processed CsPbI2 Br PSCs using a hot-casting method with precisely controlled substrate temperature. Abstract : All-inorganic cesium lead halide perovskites (CsPbX3 ) have emerged as one of the most promising photovoltaic materials due to their superior thermal stability. However, the high phase transition temperatures (typically over 250 °C) of CsPbX3 perovskites are incompatible with flexible substrates. Herein, we employ a simple hot-casting method to fabricate low-temperature processed CsPbI2 Br films. By casting the perovskite precursor solution onto a hot substrate (maintained at 55 °C), compact, large-grain and pinhole-free CsPbI2 Br films can be prepared at a low post-annealing temperature, which outperform the conventional room temperature (RT)-casting and high-temperature (post-annealing at 340 °C) processed CsPbI2 Br films containing some voids. As a result, the hot-casting and low-temperature (post-annealing at 120 °C) processed CsPbI2 Br perovskite solar cells (PSCs) exhibited an outstanding power conversion efficiency (PCE) of 12.5%, which is much higher than that (2.91%) of the RT-casting processed CsPbI2 Br devices. Further optimization of the post-annealing temperature (optimized value: 180 °C) yielded the best performance of 13.8% for hot-casting processed CsPbI2 Br devices. This study gives an effective and facile strategy toward low-temperature processed all-inorganic perovskite films and high-performance PSCs.